Assessing Clinical Effectiveness of Ceftolozane/Tazobactam, Ceftazidime/Avibactam, and Meropenem/Vaborbactam in Bacteremia: A Systematic Review and Meta-Analysis - Shahd Mohammad; Mosab Albalas; Mohammad M. Al-Ahmad (Antibiotics, 2026)
Background/Objectives: Bacteremia poses a significant clinical challenge, often necessitating the off-label use of novel β-lactam/β-lactamase inhibitor (BL/BLI) combinations such as Ceftolozane/Tazobactam (C/T), Ceftazidime/Avibactam (C/A), and Meropenem/Vaborbactam (M/V). Despite their widespread use, no conclusive data support their effectiveness in bacteremia. This meta-analysis aims to evaluate the clinical effectiveness of C/T, C/A, and M/V in treating bacteremia, with a focus on survival outcomes and clinical cure rates. Methods: A systematic review and meta-analysis were conducted following a comprehensive search of Scopus and PubMed databases. Studies reporting survival and clinical cure rates in patients treated with C/T, C/A, or M/V for bacteremia were included. Data extraction followed predefined criteria, and a random-effects meta-analysis was performed to synthesize the findings. Results: Twenty studies met the inclusion criteria, with 18 reporting survival outcomes and 10 evaluating clinical cure rates. The pooled survival and clinical cure rates were 73.6% (95% CI: 67.5–79.8%, p < 0.001) and 76.2% (95% CI: 69.2–83.3%, p < 0.001), respectively, both exhibiting moderate heterogeneity. Subgroup analyses revealed consistent survival trends across study quality, with low- and high-risk-of-bias studies demonstrating comparable estimates. Given that C/A was the most frequently studied agent, its dedicated subgroup analysis yielded a pooled survival estimate of 73.4% (95% CI: 66.4–80.3%, p < 0.001). Conclusions: This meta-analysis provides supporting evidence for the clinical effectiveness of C/T, C/A, and M/V in bacteremia reinforcing the role of BL/BLIs in antimicrobial stewardship as viable options for resistant infections. However, further randomized controlled trials (RCTs) are warranted to validate these results and refine treatment strategies for bacteremia.